INFOGRAPHIC E-BOOK DESIGN AS AN INFORMATION MEDIA FOR MOUNTAIN ROWO TOURISM IN PATI DISTRICT - Mustain, Ulin Ni’am (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2020)
The purpose of this project is to produce an infographic e-book that can be used as an educational medium for people who will visit or have visited the Waduk Gunung Rowo. This infographic e-book design method goes through several stages of work in sequence: pre-production process, production process, and post-production process. The design of this infographic e-book produces works such as: front cover, daftar isi, apa sih waduk gunung rowo itu, sejarah Waduk Gunung Rowo, fungsi Waduk Gunung Rowo, ada apa aja di Waduk Gunung Rowo, peta dan rute ke Waduk Gunung Rowo, Rowo Fact!, informasi penting saat ke Waduk Gunung Rowo, and back cover. The final product of Waduk Gunung Rowo infographic e-book has a flat design style that emphasizes a simple style of layout and color so that it is easily understood by the reader. The design of the tourism infographic e-book of Waduk Gunung Rowo is an effort to provide information to visitors, such as information about history, reservoir function, interesting spots, and so forth.